Student perceptions of governance at UNI, 2019 - Rojas Gallo, Rodolfo (2019)
The present investigation has like objective determined the perception of the student, according to his perspectives with respect to the desirable characteristics for a teacher - governor in the National University of Engineering, 2019. The general problem is how the student perceives the action of the future governing teachers UNI? The main hypothesis is that the students of the UNI, prefer anideal professor, progressive, honest and experienced in public university management. As specific objectives: find some fundamental qualities that the student wishes for the university authority that will be chosen in 2019 for deans and 2020 for Rector and Vice Rectors in the National Uni-versity of Engineering as well as some demands that the students wish. The research is a non-experimental design of a descriptive level of transectional cut (Hernández, et al, 2014). The survey technique was applied by applying a ques-tionnaire of 20 questions to a sample of 320 students selected for convenience and proportionality, from the 11 Faculties. UNI. For the results, the descriptive statistics was used by means of an ordering and previous classification in Excel and then it was processed with SPSSv25. The main conclusions were that students prefer a rector with high specialization, experience in public management and a democratic style. They also consider that educational infrastructure is important for good teaching. As for an eventual election, they do not consider any candidate who has had any link to power in the last 20 years.